KOORDINASI ANTARA MUSYAWARAH NAGARI (MUSRI) DENGAN BHABINKAMTIBMAS POLRES SAWAHLUNTO DALAM PENANGGULANGAN KEJAHATAN DI KOTA SAWAHLUNTO - Asri Joni (UNES Law Review, 2021)
The coordination between the nagari deliberation (Musri) in Sawahlunto City and the Bhabinkamtibmas of the Sawahlunto Police in dealing with crime is through unification activities carried out by Bhabinkamtibmas on the activities of the elements in Musri. Coordination is carried out to create a sense of security for the entire community, especially to anticipate crimes such as theft that often occur in Sawahlunto City. This coordination can also encourage people to exchange ideas. The existence of coordination between the Nagari Deliberation and Bhabinkamtibmas in Sawahlunto City which is carried out in each village makes it easier to control criminal acts in each region, as well as in conducting socialization, by inviting village heads and the community to submit and request information and input from the village community in Sawahlunto City. Obstacles in Empowering Nagari Deliberation Cooperation (Musri) in Sawahlunto City with Bhabinkamtibmas Sawahlunto Police in Crime Prevention include the presence of a third party who interferes in a problem, affecting the problem solving process carried out by Bhabinkamtibmas. Lack of understanding of the community towards the laws and regulations that apply so that many people who stumble into problems want to win on their own without thinking about other parties. Some of the Bhabinkamtibmas officers did not fully understand the problem-solving techniques they faced.